A Detailed Analysis of the Effect of Different Environmental Factors on Fish Phototactic Behavior: Directional Fish Guiding and Expelling Technique - Jiawei Xu; Wenlu Sang; Huichao Dai; Chenyu Lin; Senfan Ke; Jingqiao Mao; Gang Wang; Xiaotao Shi (Animals, 2022)
Optimization of light-based fish passage facilities has attracted extensive attention, but studies under the influence of various environmental factors are scarce. We established a novel experimental method to measure the phototactic behavior of Schizothorax waltoni. The results showed that S. waltoni preferred the four light colors in the order green, blue, red, and yellow. The increased flow velocity intensified the positive and negative phototaxis of fish under different light environments, while an increase in the water temperature aroused the escape behavior. The escape behavior of fish in red and yellow light and the phototaxis behavior in green and blue light intensified as the light intensity exceeded the phototaxis threshold and continued to increase. Thus, red or yellow light greater than the phototaxis threshold can be used to move fish away from high-turbulent flows or polluted waters, while green or blue light can be used to guide them to fish passage entrance or ideal habitats. This study provides scientific evidence and application value for restoring fish habitats, fish passages, and fisheries.